The welfare of farmed Nile tilapia: a review - Emam, Wasseem; Lambert, Helen; Brown, Culum (Frontiers in Veterinary Science, 2025)
Nile tilapia are, by absolute number of individuals, the most farmed species of fish today, yet we know little about how common husbandry practices impact their welfare. Despite their global importance, there is a notable lack of detailed, species-specific welfare guidelines for tilapia farming. This gap reflects the scarcity of research-based recommendations on appropriate breeding conditions, environmental parameters, and handling methods that fully consider their biology and behavioural ecology. This review explores key dimensions of Nile tilapia biology and the implications of commercial aquaculture practices on their welfare. Topics covered include common grow-out housing systems, water quality, stocking density, environmental enrichment, feeding practices, handling, transportation, and slaughter. The paper underscores the importance of developing species-specific welfare parameters and management practices to meet the welfare needs of these animals. Specifically, it describes the most common grow-out housing systems and how parameters inherent to those systems, such as stocking density and environmental enrichment, impact Nile tilapia welfare. The review singles out capture and slaughter processes as particularly detrimental to tilapia welfare and offers insight into how evidence-based approaches can enhance welfare in commercial farming operations.